Komparasi Kewenangan Pengadilan Negeri Surabaya Dalam Sengketa Ekonomi Syariah Perspektif Kepastian Hukum - Abd Hafid Hafid (MASADIR: Jurnal Hukum Islam, 2023)
Judicial power is a judicial institution that is given the authority to resolve a dispute in this matter, the Supreme Court which oversees four judicial bodies under it. In Surabaya District Court decision between case No: 622 Pdt.G/2021/PN. Sby and case No: 835 Pdt.Bth/2021/PN. Sby is one subject of law and the same object of law, but in the decision of the Court raises a different (contradictory) ruling. This article examines a comparative study of the theory of legal certainty review of court decisions. In this article, the author uses research methods with an approach to court decisions, literature, laws. In Surabaya district Court decision, there are two different decisions, The First, the court decision with Register No: 622 Pdt.G/2021/PN. Sby stated that he did not have absolute authority in accordance with applicable laws and regulations, The Second, the decision of the Court, with Register No. 835 Pdt.Bth/2021/PN. Sby has absolute authority, this is not in accordance with the laws and regulations The theory of legal certainty is one of the most important legal principles in the legal system in many countries, including Indonesia, This theory refers to the principle, that the law must be clear, certain, and understandable by all people or citizens who are subject to the law, so that in the judgment the court gives rise to contradictory decisions, the first decision is in accordance with applicable legal regulations, while the second decision is not in accordance with legal regulations.